Pengaruh harga, kualitas produk dan brand image terhadap keputusan pembelian - Hertina, Dede; Wulandari, Denisa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Indonesian people are now using skin care products to maintain healthy skin. This concern about skin beauty care has become a trend and needs of most Indonesian people, both men and women. Due to this trend, the growth of the beauty industry, especially skin care, is increasingly marked by the emergence of various skin care brands. This researcher aims to analyze the effect of price, product quality and brand image on purchasing decisions. This study uses quantitative research methods with questionnaire survey techniques. The population of this study were consumers of skincare products from the Dabe Beauty brand, Bandung regency agent, with a population of 40 people using the purposive sampling method, the number of samples obtained was 35 people. The results of the study simultaneously stated that price, product quality and brand image had a significant effect on purchasing decisions for Dabe Beauty brand skincare products, Bandung Regency agents. While the results of the study partially state that price, product quality and brand image have a positive and significant effect on purchasing decisions.